Studying digestion conditions of Vietnamese monazite with acid sulfuric for the recovery of rare earth elements, thorium and uranium - Luu , Xuan Dinh; Nguyen, Van Tung; Nguyen, Van Phu; Nguyen, Phuong Thoa; Tran, Hoang Mai (Nuclear Science and Technology, 2018)
The monazite ore is a commercial source of Th, U and rare earth in Vietnam. There are two methods, which were often applied to decompose monazite ore are alkaline and sulfuric methods. But in Vietnam, sulfuric method is more suitable due to the simple technology. In sulfuric acid treatment its breakdown using sulfate process for recovering of REEs, thorium and uranium. In this study, the parameters such as ore/acid ratios, the digestion temperature and the time of degestion were investigated to determine optimal digestion conditions for high recovery of main ingredients (REEs, Th, U) in monazite ore. The results shown that the optimal parameters for the digestion are ore/acid ratio 1.2:1, digestion temperature - 300oC and time of digestion - 1 hour, the recoveries for REEs, Th and U are namely 90%, 85% and 65%, respectively.